2019
DOI: 10.1093/jxb/erz270
|View full text |Cite
|
Sign up to set email alerts
|

CEP3 levels affect starvation-related growth responses of the primary root

Abstract: CEPs (C-TERMINALLY ENCODED PEPTIDEs) inhibit Arabidopsis primary root growth by unknown mechanisms. We investigated how CEP3 levels control primary root growth. CEP3 peptide application decreased cell division, S-phase cell number, root meristematic cell number, and meristem zone (MZ) size in a dose- and CEP RECEPTOR1-dependent manner. Grafting showed that CEP3-dependent growth inhibition requires root and shoot CEPR1. CEP3 induced mitotic quiescence in MZ cells significantly faster than that induced by nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 53 publications
(90 reference statements)
1
41
0
Order By: Relevance
“…Prior publications reported that CEPR1 controls local (root) and systemic (shoot) LR growth in Arabidopsis whereas CRA2 controls LR number locally in Medicago (Huault et al , 2014; Tabata et al , 2014; Mohd‐Radzman et al , 2015; Roberts et al , 2016; Chapman et al , 2019; Delay et al , 2019; Laffont et al , 2019). Therefore, we grafted hypocotyls of Arabidopsis WT and cepr1 mutants and Medicago A17 and cra2‐11 to determine if the CEP receptor controls the GSA from the root and/or the shoot (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior publications reported that CEPR1 controls local (root) and systemic (shoot) LR growth in Arabidopsis whereas CRA2 controls LR number locally in Medicago (Huault et al , 2014; Tabata et al , 2014; Mohd‐Radzman et al , 2015; Roberts et al , 2016; Chapman et al , 2019; Delay et al , 2019; Laffont et al , 2019). Therefore, we grafted hypocotyls of Arabidopsis WT and cepr1 mutants and Medicago A17 and cra2‐11 to determine if the CEP receptor controls the GSA from the root and/or the shoot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is notable as some other CEP–CEP receptor‐mediated processes that control root growth (e.g. main root growth, LR growth and density) were not entirely congruent between Medicago and Arabidopsis (Delay et al , 2013, 2019; Imin et al , 2013; Huault et al , 2014; Tabata et al , 2014; Djordjevic et al , 2015; Mohd‐Radzman et al , 2015, 2016; Roberts et al , 2016; Chapman et al , 2019; Laffont et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AtCEP3 was shown to be activated in the root upon nitrogen deficiency. Moreover, a mutant defective in the AtCEP3 gene exhibited more developed root system under different stress factors (for example, nitrogen deficiency or salination) as compared with wild-type plants; on a standard medium, it did not show differences comparing with wild-type plants [76]. These data suggest that CEP peptides (and especially AtСЕР3) act as negative regulators of root-system development under stress conditions.…”
Section: Regulation Of Cep Expression By Nitrate and Other Agentsmentioning
confidence: 80%
“…The identification of CEP receptors 1 and 2 (CEPR1 and CEPR2) in Arabidopsis suggested that sensing of root-derived CEP peptides by these shoot receptors mediates systemic nitrogen-demand signaling (Tabata et al, 2014). Application of CEP3 peptide decreases cell division, S-phase cell number, root meristematic cell number, and meristem zone (MZ) size in a dose- and CEPR1-dependent manner, especially under severe nutrient limitation (Delay et al, 2019). In Medicago , MtCEP1 is expressed in primary root tips, vascular tissue, and lateral organ primordia, particularly under nitrogen (N) limitations (Imin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%